C-H activation of methane to formaldehyde on Ce1-xZrxO2 thin films: a step to bridge the material gap - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (ChemCatChem, 2016)
Ce1−xZrxO2 (CZ) thin films were prepared by a combination of sol–gel and spin-coating methods and were evaluated for the C−H activation of methane by using a molecular beam set-up with the aim to bridge the material gap. The C−H activation of methane begins at 950 K, and a Ce-rich CZ composition displays a high selectivity (4–12 %) to the partially oxidised product, formaldehyde. A 10–12 % selectivity towards HCHO with 1.6 % methane conversion was observed with methane-rich CH4/O2 reactant compositions at 1050 K. Short contact times, prevalent under molecular beam conditions, could be a possible reason for HCHO formation. Although combustion products were observed instantly upon shining the mixture of reactants on CZ surfaces, up to 20 s delay was observed before formaldehyde generation, which indicates that the oxygen vacancy migration contributes to the rate-determining step and the diffusion-controlled nature of the reaction. A burst in HCHO generation at the point of molecular beam opening, after beam-closed conditions, suggests that the diffusion of oxygen vacancies to the surface is the reason for HCHO formation. Kinetics results also indicate the necessity of reduction sites for HCHO generation.